Depression – A major but neglected consequence contributing to the health toll from prescription opioids?. (30th September 2016) - Fischer, Benedikt; Murphy, Yoko; Kurdyak, Paul; Goldner, Elliot M.
Abstract: Prescription opioid analgesic (POA) use is common especially in North America, and associated with extensive morbidity and mortality. While medical and non-medical POA use have been documented to be associated with mental health problems, and specifically depression, newly emerging epidemiological evidence suggests that incident depression post-initiation of POA use may be common. Neurobiological – specifically regarding impacts of POAs on brain functioning – and/or psycho-social processes may be relevant pathways; these must be better understood, also to guide clinical practice for interventions. Incident depression outcomes may be an added component to the extensive health toll from widespread POA use. Highlights: Prescription opioid analgesic (POA) use and harms are high in North America. Several epidemiological studies show links between POA use/misuse and depression. Select recent studies found evidence for incident depression following POA use. Neurobiological evidence suggests plausibility for a POA use and depression link. Attention to the public health toll of POAs including depression is needed.